Analisis Perkembangan Sikap Prososial Anak Usia Dini Menurut Bandura - Hifni, Cici; Sit, Masganti (Asian Journal of Early Childhood and Elementary Education, 2024)
The formation of prosocial attitudes in early childhood has a significant impact on the formation of their character and behavior in the future. The role of the model and environmental influences are important factors in this process. This research aims to explore more deeply the role of models and environmental influences in the formation of prosocial attitudes in young children, as well as to understand the challenges and obstacles faced in efforts to promote prosocial behavior in them. The research method used is qualitative research, by conducting direct observations and in-depth interviews with parents, teachers and children's caregivers. Data were analyzed thematically to identify key patterns and findings. The research results show that the role of models, whether from parents, teachers, or characters in the media, has a significant impact in shaping the prosocial attitudes of young children. The environment, including at home, at school and in the community, also plays an important role in shaping children's behavior. However, there are challenges such as negative media content and lack of awareness about the importance of promoting prosocial attitudes in early childhood. Therefore, a deep understanding of these factors is key in creating an environment that supports positive moral and social development in early childhood.